The Influence of Audit Technology on Audit Efficiency and Effectiveness: Auditor’s Perspective - Herts Taunaumang; Rafaela Lima; Raul Gomez (Yayasan Adra Karima Hubbi, 2025)
The rapid advancement of audit technology, including data analytics, artificial intelligence (AI), and blockchain, has significantly transformed the auditing profession. These technologies promise to enhance audit efficiency and effectiveness by automating routine tasks, improving data accuracy, and enabling deeper insights. However, the extent to which these technologies influence audit outcomes from the auditor's perspective remains underexplored, particularly in terms of their practical implementation and perceived benefits. This study aims to examine the influence of audit technology on audit efficiency and effectiveness from the perspective of auditors, focusing on their experiences, challenges, and perceived outcomes. A mixed-methods approach was employed, combining surveys and semi-structured interviews with auditors from public accounting firms. Quantitative data were analyzed using statistical techniques, while qualitative data were thematically analyzed to identify key patterns and insights. The findings reveal that audit technology significantly improves efficiency by reducing time spent on manual tasks and enhancing data processing capabilities. Auditors also reported increased effectiveness, as technology enabled better risk assessment, fraud detection, and compliance monitoring. However, challenges such as high implementation costs, skill gaps, and resistance to change were identified as barriers to full adoption. The study concludes that audit technology has a transformative impact on audit efficiency and effectiveness, but its successful integration requires addressing technical, organizational, and human factors.